Factors affecting recruitment to an observational multicentre palliative care study. Issue 3 (7th January 2013) - Stone, Patrick C; Gwilliam, Bridget; Keeley, Vaughan; Todd, Chris; Kelly, Laura C; Barclay, Stephen
Abstract : Objectives: To identify those factors which adversely affected recruitment to a large multicentre palliative care study. Methods: Patient accrual to a multicentre, observational, palliative care study was monitored at three critical junctures in the research process. (1) Eligibility—did the patient fulfil the study entry criteria? (2) Accessibility—was it possible to access the patient to be able to inform them about the study? (3) Consent—did the patient agree to participate in the study? The reasons why patients were ineligible, inaccessible or refused consent were recorded. Results: 12 412 consecutive referrals to participating clinical services were screened for study inclusion of whom 5394 (43%) were deemed to be ineligible. Of the remaining patients 4617/7018 (66%) were inaccessible to the research team. The most common reasons being precipitous death, 'gatekeeping' by clinical staff or rapid discharge. Of the 2410 patients who were visited by the research team and asked to participate in the study 1378 (57%) declined. Overall 8.2% (1018/12 412) of patients screened participated in the study. There were significant differences in recruitment patterns between hospice inpatient units, hospital support and community palliative care teams. Conclusions: Systematic monitoring and analysis of patient flows through the clinical trial accrual process provided valuable insights about the reasons for failure to recruit patients to a clinical trial and may help to improve recruitment in future studies.